Diretrizes para práticas de qualidade nas diferentes etapas do processo de produção de lajes alveolares de concreto protendido - Direitinho, Romão Manuel Leitão Carrapato (Universidade Federal de São Carlos, 2015)
Industrialization in the Brazilian construction industry is a growing trend, while the need to fulfill tight deadlines increases as well as labor costs, being mandatory to keep quality standards and the competitiveness of enterprises. In this sense, the precast concrete is an increasingly valid solution.Among him, the floor in hollow core slabs of prestressed concrete, as part of a constructive system of open cycle. This kind of floor can be applied in various sectors and to the most varied typologies. The ABNT NBR 14861: 2011 is still quite new, and includes a set of quality control care for the implementation of hollow core slabs in prestressed concrete, although it is felt that the respective degree of detail could be improved.On the other hand, the standard has just focusing on such care specially concerning project and product approaches, and not so much with a process approach. There is also some difficulty in the flow of information and knowledge between the academy and industry in general. The dissertation provides a detailed analysis of production of hollow core slabs in prestressed concrete, according to the respective processes, since the inputs enter factories, until the structural cover is performed on site. The macro-production process is divided into several stages of lower complexity, and contains a detailed listing of quality control procedures required, in a simple and practical manner. Thus, can be established a kind of a guide to good quality control practices for the production of LACP, which is then systematized through a set of checklists. The establishment of guidelines for good quality control practices in the various LACP production stages is the main goal of this research. In order to accomplish this goal have been made extensive literature reviews on Quality and hollow core slabs, using theses, dissertations, monographs, papers, magazines and electronic sites. Were also made visits to a factory which produces equipment for production of hollow core slabs, and to a plant producing LACP, in the interior of the state of São Paulo, during which were made unstructured interviews with their maximum management responsables. Finally it was made an essentially qualitative comparative analysis of the data collected and the quality control procedures of the ABNT NBR 14861: 2011. It is intended, with the checklists contained in the dissertation, to ensure production, transportation to site, installation of LACP and execution of the respective structural wrapper, with the highest quality consistency that is possible, thereby minimizing to minimum the existence of possible non-compliances.
Keywords: Laje alveolar; Pré-moldado; Processo de produção; Controle de qualidade; Hollow core slabs; Precast; Production process; Quality control; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL